Success of network building in community prevention and control of Dengue Hemorrhagic Fever in community: a case study of Ta Din Daeng Sub-District, Phak hai District, Phra Nakorn Si Ayutthaya Province. - วงษ์พิรา, นันท์นภัส; พะยอมยนต์, พายัพ (Disease Control Journal, 2014)
Research on the Success of Network Building to Prevention and Control Dengue Hemorrhagic Fever in Community: A Case Study of Ta Din Daeng Sub-District, Phak Hai District, Phra Nakhon Si Ayutthaya Province comprised of 4 objectives. First, to study the process of building the network. Second, to study the management of the network. Third, to study the factors that affect the success of the network. And fourthly, to study the obstacles of building and managing networks. Which is a qualitative research. The samples used in this study consists of a network of groups in the community, a person whose role is significant in propelling and developing prevention and control of dengue in a community of 10 people. Regarding techniques and tools used in the experiment are; Interviews and group discussion, using the descriptive analysis. The results were as follows: (1) Create a network of prevention and control of dengue in the community. The effect from experiencing an outbreak of dengue fever in the community is the start of an integration of community members to seek for solutions to the problems. Regarding processes and important steps of establishing a network comprised of four stages: (a) the awareness to solve the problems in the community, (b) to create a network to prevent and control dengue community (c) the development of procedures and appropriate standards to prevent disease, and (d) expanding the operations to other communities. (2) Network management model for the prevention and control of dengue in the community found that: It is operated in the committee format with representatives from all sectors of the community. The Significant configuration in network management consists of: Usage of key strategic in operating. Communications between the community members. The exchanging and transferring of knowledge. And management of community resources (3) Factors affecting the success of the prevention and control of dengue in the community was found that the major factor affecting the success of the network consists of a common goal; Participation of network members; Empowerment of the network; Exchange interaction and the mobilization of resources for implementation. Thus, it was also found that the community leaders and volunteers is an example of a sacrifice and together take action to make the community a considerate and cooperate in the activities. (4) The obstacles which affect the establishment and implementation of networks in the community to prevent and control dengue fever were; overload responsibilities of community members, the lack of public spirit of the community, flooding in the area and budget to support the operations is insufficient.